Pengaruh Kompensasi Finansial Langsung Terhadap Kinerja Karyawan Pada Percetakan Marisa Baru: The Effect of Direct Financial Compensation on Employee Performance At The New Marisa Printing - Rahmad Rifaldi D. Ladia; Heny Ariwijaya; Ichsan Milang (Jurnal Ilmiah Produktif, 2022)
The impact of the lack of good human resources on organizational effectiveness is much greater than that of other resources. Good human resource management will determine the success of the organization in the future. Or vice versa, poor management of human resources will have an impact on not achieving organizational work effectiveness. Employee performance needs more attention from the organization because if employee performance increases in the organization, the impact on organizational productivity will be achieved so that the organization can run well and will continue to grow. The purpose of this study was to determine how to direct financial compensation effect employee performance at Marisa Baru Printing. The type of data used in this study is the type of qualitative data that is quantified and the data sources used are primary data sources. The sampling technique in this study used the saturated sampling method, totaling 18 samples. The results of the simple linear regression equation Y=11+0.5x. The correlation coefficient is 0.528, the determination coefficient is 0.278. The results showed that there was a significant effect of direct financial compensation on employee performance at Marisa Baru Printing.